Dataset for AABS baseline/characterization in Kenya (wp3) - Manyise, Timothy; Brako Dompreh, Eric; Juma, Fredrick; Ogello, Erick; Muthoka, Mavindu; Munguti, Jonathan (2025)
This baseline study was conducted in October 2024 as part of the Asia Africa BlueTech Superhighway project. The study comprised of different modules: demographic characteristics, personal characteristics, market dynamics, fish loss assessment, current postharvest practices and challenges, climate and environment, training and capacity building on postharvest technologies, food and nutrition, gender empowerment, and poverty.